2007
DOI: 10.3892/or.17.5.1109
|View full text |Cite
|
Sign up to set email alerts
|

Hypoploidy defines patients with poor prognosis in breast cancer

Abstract: The clinicopathological features currently used in breast cancer prognosis often fail to characterize the clinical heterogeneity of the disease accurately. Our study is aimed to investigate the predictive value of DNA flow cytometry in breast cancer. Previously untreated breast carcinoma samples (584) were snap frozen for flow-cytometry. Tumors were classified into three DNA index (DI) categories: i) tumors showing a DI =0.96-1.15 (diploid and near-diploid); ii) tumors with a DI ≥1.16 (hyperdiploid, tetraploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Given our prior finding of DNA ploidy as an indepdent prognostic factor for overall survival of breast cancer patients [11] , we further classified ER−&PR− tumors by their DNA index and evaluated the association of family history and these tumor subtypes ( Table 5 ). Family history was more pronouncedly associated with diploid/near-diploid ER−&PR− tumors (OR, 2.17; 95% CI, 0.99–4.74) than aneuploid ER−&PR− tumors (OR, 1.23; 95% CI, 0.73–2.08).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given our prior finding of DNA ploidy as an indepdent prognostic factor for overall survival of breast cancer patients [11] , we further classified ER−&PR− tumors by their DNA index and evaluated the association of family history and these tumor subtypes ( Table 5 ). Family history was more pronouncedly associated with diploid/near-diploid ER−&PR− tumors (OR, 2.17; 95% CI, 0.99–4.74) than aneuploid ER−&PR− tumors (OR, 1.23; 95% CI, 0.73–2.08).…”
Section: Resultsmentioning
confidence: 99%
“…The study involved 663 women with operable invasive breast cancer diagnosed and treated between April 1991 and December 2005 at the Clinical University Hospital of Santiago de Compostela (Santiago de Compostela, Spain) [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the original analysis of the dataset (Chavez-Uribe et al, 2007), the authors categorized the variable DI into three groups, i.e., Group I diploid (0.96 ≤ DI ≤ 1.15), Group II hyperploids (DI ≥ 1.16) and Group III hypoploids (DI ≤ 0.95), and they concluded that the patients with hypoploid tumours had a worse prognosis. From the biologic point of view, clinicians expect that tumours with DI values close to 1 will have a better prognosis than those distant from 1.…”
Section: Multi-state Modelling Approachmentioning
confidence: 99%